Methylene Blue in the Treatment of Neuropsychiatric Disorders - Alda, Martin (CNS drugs, 2019)
Methylene blue is a long-established drug with complex pharmacology and multiple clinical indications. Its diverse mechanisms of action are most likely responsible for the large variety of its clinical effects. Of interest to psychiatrists, methylene blue has antidepressant, anxiolytic, and neuroprotective properties documented by both animal and human studies. Its stabilizing effect on mitochondrial function and dose-dependent effect on the generation of reactive oxygen species are of significant heuristic value. For these reasons, methylene blue holds promise as a proof-of-concept treatment of organic/neurodegenerative disorders and as a neuroprotective agent in general. In psychiatry, methylene blue has been used for over a century. It was tried successfully in the treatment of psychotic and mood disorders and as a memory enhancer in fear-extinction training. Particularly promising results have been obtained in both short- and long-term treatment of bipolar disorder. In these studies, methylene blue produced an antidepressant and anxiolytic effect without risk of a switch into mania. Long-term use of methylene blue in bipolar disorder led to a better stabilization and a reduction in residual symptoms of the illness. It is usually well tolerated, but caution is needed in the light of its inhibitory effect on monoamine oxidase A.
Keywords: Methylene Blue; Fear; Humans; Neuroprotective Agents; zvířata; Antidepressive Agents; Bipolar Disorder; strach; bipolární porucha; methylenová modř; Animals; antidepresiva; lidé; neuroprotektivní látky